2009
DOI: 10.1089/acm.2008.0414
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from the Cochrane Collaboration for Traditional Chinese Medicine Therapies

Abstract: Background The Cochrane Collaboration, an international not-for-profit organization that prepares and maintains systematic reviews of randomized trials of health care therapies, has produced reviews summarizing much of the evidence on Traditional Chinese Medicine (TCM). Our objective was to review the evidence base according to Cochrane systematic reviews. Methods In order to detect reviews focusing on TCM, we searched the titles and abstracts of all reviews in Issue 4, 2008 of the Cochrane Database of Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 32 publications
0
59
0
4
Order By: Relevance
“…In addition, they are expensive. Accordingly, an increasing number of patients with RA and other diseases in developed countries are using natural products and other complementary and alternative medicine (CAM) approaches for their healthcare needs [2][3][4][5][6]. These CAM products and services belong to various traditional systems of medicine, such as traditional Chinese medicine (TCM).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, they are expensive. Accordingly, an increasing number of patients with RA and other diseases in developed countries are using natural products and other complementary and alternative medicine (CAM) approaches for their healthcare needs [2][3][4][5][6]. These CAM products and services belong to various traditional systems of medicine, such as traditional Chinese medicine (TCM).…”
mentioning
confidence: 99%
“…Herbal products and acupuncture are the most commonly used forms of TCM, which also includes moxibustion, tai chi and other modalities [5]. The application of TCM in RA is based on the categorization of patients according to distinct TCM patterns of Bi syndrome, based on cold and hot patterns, the level of vital energy (Q i ) and other criteria.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, a review of a total of 70 Cochrane systematic reviews regarding TCM clinical research found most of the studies to be inconclusive 10 . Reasons were multiple.…”
Section: Rheumatologymentioning
confidence: 99%